BASLAWÍSH BILIMLENDIRIW SABAQLÍQLARÍ TEKSTLERINIŃ INFORMACIYALÍQ BAZASÍN DÚZIW MÁSELELERI - Xojanov, B.; Ixlasov, I. (SCIENCE and SOCIETY, 2022)
This paper outlines the need for regular updating of learning technologies and the preparation of modern textbooks that suit them at the system of Public Education.